(untitled) (Fiep Bulletin - online, 2025)
Introduction: Swimming is a time-trial sport where performance is measured by the athlete’s ability to swim distances in the shortest time possible. In this sport, many factors influence performance and choosing the best race strategy is essential for athletes to succeed. Objective: To investigate whether the choice of race strategy is related to the performance of elite athletes in 200-meter backstroke events. Methods: The results of 18 races (9 male and 9 female athletes) across nine events (three Olympic Games and six World Swimming Championships) from 2009 to 2020 were analyzed. Results: In both categories, swimmers completed the first lap faster than the remaining laps. However, only the men showed a significant difference between the first lap time and the total time. Additionally, a negative correlation was identified in the first half of the race (100 meters) and a positive one in the second half, for both sexes. Conclusion: Swimmers tend to adopt a positive strategy: starting with a fast first lap, followed by a decrease in speed on the second lap, and an increase in speed in the final laps, culminating in a final sprint. This strategy is recognized in the literature as the most effective, taking advantage of easier breathing and reduced water resistance. These findings provide guidance for coaches to integrate this approach into their training programs, aiming to improve their athletes’ performance.